Water pricing and its role in achieving efficient use in Algeria – an analytical study - - عقون , شراف; Kamel, Zemmori; Lefilef, Abdelhak (Finance and Business Economies Review, 2017)
For the water scarcity, increased demand and the high cost of developing sources of new water, Algeria Consider approaches manage their water resources, and make them resort to some modern methods that aim to increase the volume of water supply and development and improve the pattern of use and raise their efficiency, and based on the application of strategic integrated management of water resources that based on the entrance of demand management, The way is to "water pricing", which is a key tool in the field of rational use to be this pricing gathering the cost of production and distribution of water and the level of disposable income users, and ensure the latter raise the efficiency and effectiveness of water use . In order to understanding the aspects of the subject, this research comes, trying to show the impact of pricing on the rational use of water and through exposing the following sections: 1 - Economic Analysis of water; 2 - marketing dimensional of pricing; 3 - water pricing in the modern trend towards water demand management; 4 - Water Pricing in Algeria and their development.